A review on the implementation of problem-based learning in English language learning - Abu Bakar, Noor Idayu; Noordin, Nooreen (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Problem-based learning (PBL) has been recognised as an effective method of teaching and learning. The possibility of integrating PBL in language learning is established in the discussions by Mardziah (1998), Larsson (2001), Mathews-Aydinli (2007) and Boothe, Vaughn, Hill and Hill (2011). Alongside the discussions, many researchers have also embarked on PBL research in English language learning. This conceptual paper aims to review the current empirical studies of PBL in the area of English language education in the literature. It attempts to provide readers with the current state of knowledge in the field by highlighting areas of PBL studies in English language learning, methodologies employed in the studies and significant findings by the previous researchers. In the last part of the paper, the researcher also identifies gaps in the studies in order to create space for further research in the field.